First case series of clozapine induced hypogammaglobulinaemia in England - S Elkhalifa; T Garcez; S Drinkwater; T Tan; P Vijayadurai; A Anantharachagan; A Herwadkar; H Alachkar; J Darroch (Annals of Psychiatry and Treatment - Peertechz Publications, 2021)
Evidence is emerging that clozapine can adversely affect immunoglobulin levels. We present a case series of 17 clozapine-treated patients referred to clinical immunology centres in the north west of England with otherwise-unexplained hypogammaglobulinaemia. This adds to existing evidence and suggests that clozapine can cause clinically significant antibody deficiency that will sometimes require specialist intervention. We speculate that this putative drug toxicity could be mediated via interaction with PI3K (phosphatidylinositol-3-kinase) signalling pathways involved in the development and homeostasis of B cells. It may be advisable to monitor immunoglobulin levels in patients being treated with clozapine.